Effect of Moxibustion Treatment on Degree Centrality in Patients With Mild Cognitive Impairment: A Resting-State Functional Magnetic Resonance Imaging Study - Xu, Ke; Wei, Yichen; Liu, Chengxiang; Zhao, Lihua; Geng, Bowen; Mai, Wei; Zhang, Shuming; Liang, Lingyan; Zeng, Xiao; Deng, Demao; Liu, Peng (Frontiers in Human Neuroscience, 2022)
Purpose: Mild cognitive impairment (MCI) is a common neurological disorder. Moxibustion has been shown to be effective in treating MCI, but its therapeutic mechanisms still remain unclear. This study mainly aimed to investigate the modulation effect of moxibustion treatment for MCI patients by functional magnetic resonance imaging (fMRI). Methods: A total of 47 MCI patients and 30 healthy controls (HCs) participated in resting-state functional magnetic resonance imaging (rs-fMRI) scans. Forty seven MCI patients were randomly divided into true moxibustion group (TRUE, n=30) and sham moxibustion group (SHAM, n=17). The degree centrality (DC) approach was applied to distinguish altered brain functions. Correlation analysis was then performed to examine relationships between the neuroimaging findings and clinical symptoms. Results: Compared with HCs, MCI patients mainly showed decreased DC in the left middle frontal cortex (MFC) and bilateral middle cingulate cortex (MCC). After moxibustion treatment, SHAM group had no significant DC findings while TRUE group mainly showed significant increased DC in the bilateral MFC and MCC as well as decreased DC in the left middle occipital cortex (MOC). Repeated measures ANOVA showed significant interactions between the two groups of MCI patients. In addition, higher Mini-Mental State Examination (MMSE) score was significantly positively correlated with increased DC in the right MFC and left MCC after moxibustion treatment. Conclusion: Our findings demonstrate that the potential value of moxibustion treatment on MCI, which adds new insights into the popular view that moxibustion treatment may slow cognitive decline in MCI patients.